2018
DOI: 10.3233/jad-170994
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Marrow-Derived Microglia-Like Cells Ameliorate Brain Amyloid Pathology and Cognitive Impairment in a Mouse Model of Alzheimer’s Disease

Abstract: Microglia, the primary immune cells in the brain, sense pathogens and tissue damage, stimulate cytokine production, and phagocytosis to maintain homeostasis. Accumulation of amyloid-β peptides (Aβ) in the brain triggers the onset of Alzheimer's disease (AD). Accordingly, promotion of Aβ clearance represents a promising strategy for AD therapy. We previously demonstrated that primary-cultured rat microglia phagocytose Aβ, and that transplantation of these cells ameliorates the Aβ burden in brains of Aβ-injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…The cytokine stimulates the clearance of Aβ 42 by microglia and in ltrating bone marrow-derived cells (17). In line with these ndings, hippocampal injection of mCSF in AD mouse model induced the differentiation of bone marrow cells into bone marrow-derived microglia (BMDM), which resulted in improved cognitive decline (18). IL-34, triggering receptor expressed on myeloid cells 2 (TREM2) and its adaptor DNAX-activating protein of 12 KDa (DAP12) have also an important role in the pathology.…”
Section: Introductionmentioning
confidence: 62%
“…The cytokine stimulates the clearance of Aβ 42 by microglia and in ltrating bone marrow-derived cells (17). In line with these ndings, hippocampal injection of mCSF in AD mouse model induced the differentiation of bone marrow cells into bone marrow-derived microglia (BMDM), which resulted in improved cognitive decline (18). IL-34, triggering receptor expressed on myeloid cells 2 (TREM2) and its adaptor DNAX-activating protein of 12 KDa (DAP12) have also an important role in the pathology.…”
Section: Introductionmentioning
confidence: 62%
“…As monocyte‐derived repopulating cells would have a potentially different response to systemic stimuli compared to normal repopulating microglia, this is also an issue to contemplate. In contrast, it has been shown that bone marrow‐derived cells are much more efficient in clearing amyloid beta deposits compared to their endogenous counterparts (Kawanishi et al, ; Simard, Soulet, Gowing, Julien, & Rivest, ) and so monocyte repopulation would potentially be more efficient in AD.…”
Section: Enforced Microglial Repopulation: a New Prospect For Fixing mentioning
confidence: 98%
“…In addition to the molecular mediators secreted by bone, bone marrow-derived cells were identified to enter the systemic circulation and migrate into the injured brain [ 8 ]. In preclinical studies, bone marrow-derived microglia-like cells were shown to modulate amyloid pathology by restricting Aβ plaque formation and by supporting Aβ plaque clearance, which improved cognitive impairment [ 366 , 367 , 368 ]. Therefore, recent attempts employed hematopoietic stem cells mobilized from bone marrow into the peripheral blood for autologous microglia-like cell preparation [ 369 ], using specific antibodies to convert bone marrow cells into trafficking microglia-like cells [ 367 ].…”
Section: Molecular Bases Of Brain-bone Crosstalkmentioning
confidence: 99%